Study on Myths in Some Selected Plays of English and English Translation as a Cultural Discourse: Exploring the Influence of Myths in English Plays: A Discourse Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Myths are generally seen as narratives or stories (mythos) that have taken place in a primordial age. They are stories involving superhuman desires and strivings, human accomplishments and limitations. A fantasy must have both narrative power (i.e. it should be a decent story) and functional relevance (i.e. it must say or safeguard something important). Since myths establish models for behavior, their major function is didactic. Myths often function to maintain social structures and institutions they legitimize societal sets of accepted rules by claiming that they were established by sacred beings and through their function as the cultural storehouse. Creative journalists in all ages have been influenced by myths and thus they adapted myths extensively. Despite the fact that myths are culture specific, they gain allegorical and metaphorical value and new significance during the time spent adaptation and appropriation. Henceforth even modern playwrights have not been impenetrable to this influence. Familiarity of ancient myths to contemporary readers and probability of infusing new meanings into them make myths a viable device in the hands of the modern playwrights. Literary works draw upon a common store of archetypes or intermittent images, sacred objects, or cycles of culture. In the present research study has examined myths from the point of perspective of discourse in the selected plays, some of which are composed in English and others have been translated into English.